Host Adaptation in Legionellales Is 1.9 Ga, Coincident with Eukaryogenesis. (15th February 2022) - Hugoson, Eric; Guliaev, Andrei; Ammunét, Tea; Guy, Lionel
Abstract: Bacteria adapting to living in a host cell caused the most salient events in the evolution of eukaryotes, namely the seminal fusion with an archaeon, and the emergence of both mitochondrion and chloroplast. A bacterial clade that may hold the key to understanding these events is the deep-branching gammaproteobacterial order Legionellales— containing among others Coxiella and Legionella— of which all known members grow inside eukaryotic cells. Here, by analyzing 35 novel Legionellales genomes mainly acquired through metagenomics, we show that this group is much more diverse than previously thought, and that key host-adaptation events took place very early in its evolution. Crucial virulence factors like the Type IVB secretion (Dot/Icm) system and two shared effector proteins were gained in the last Legionellales common ancestor (LLCA). Many metabolic gene families were lost in LLCA and its immediate descendants, including functions directly and indirectly related to molybdenum metabolism. On the other hand, genome sizes increased in the ancestors of the Legionella genus. We estimate that LLCA lived approximately 1.89 Ga, probably predating the last eukaryotic common ancestor by approximately 0.4–1.0 Gy. These elements strongly indicate that host adaptation arose only once in Legionellales, and that these bacteria were using advanced molecular machinery to exploit and manipulate host cells early in eukaryogenesis.